Peningkatan Hasil Belajar Bahasa Indonesia melalui Media Audiovisual pada Siswa Kelas III Sekolah Dasar - Yulinda, Tita (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This Classroom Action Research is to improve learning outcomes of Indonesian language lessons on the theme of growth and development of living things in third grade students of SD Negeri Karangbandung 02, Keanggungan District, Brebes Regency using audiovisual media. In this model, classroom action research is carried out through four stages, namely planning, action implementation, observation, and reflection and is carried out in two cycles. From this class action research, it was obtained that the average pre-cycle score of students was 59.64 with a completeness percentage of 39.28%. In the first cycle it increased to 63.21 with a completeness percentage of 57.14%. In the second cycle the average score of students became 66.96 with a completeness percentage of 71.42%. Based on the data obtained, it can be concluded that the use of audiovisual media can improve learning outcomes of Indonesian language with the theme of growth and development of living things in third grade students of SD Negeri Karangbandung 02, Keanggungan District, Brebes Regency.